Adiponectin Expression Is Modulated by Long-Term Physical Activity in Adult Patients Affected by Cystic Fibrosis - Polito, Rita; Nigro, Ersilia; Elce, Ausilia; Monaco, Maria Ludovica; Iacotucci, Paola; Carnovale, Vincenzo; Comegna, Marika; Gelzo, Monica; Zarrilli, Federica; Corso, Gaetano; Castaldo, Giuseppe; Daniele, Aurora (Mediators of Inflammation, 2019)
Cystic fibrosis (CF) is a genetic disease characterized by progressive decline of lung function and chronic airway inflammation. Adipose tissue, through adiponectin and leptin, exerts several effects on energy metabolism and inflammatory processes. This study evaluated the levels of adiponectin and leptin in adult healthy subjects, in patients with CF and their correlation with long-term physical activity. CF patients were divided into two groups (sedentary versus active) based on their regular physical activity over 3 years. Anthropometric and serum biochemical profiles of CF patients and controls were evaluated and compared. Total serum adiponectin and leptin levels were measured by ELISA; adiponectin oligomeric profiles were analysed by western blot. Adiponectin levels were significantly higher while leptin levels were lower in patients with CF than in healthy controls. Furthermore, adiponectin was significantly lower in active compared to sedentary CF (p=0.047), while leptin was slightly increased in active compared to sedentary CF. In addition, C-reactive protein levels were significantly lower in active than in sedentary CF patients (p=0.048). Interestingly, only in the active group adiponectin levels were inversely correlated with forced expiratory volume (FEV) 1% decrease/year and FEV1% decrease. Moreover, adiponectin levels negatively correlated with lipid profiles. Our findings indicated that regular, long-term physical activity in CF improves respiratory function, metabolism, and inflammation status. These improvements in patients’ conditions are associated with immunometabolic processes involving adiponectin, leptin, and C-reactive protein. Therefore, we propose that both adipokines may be a useful biomarker in the evaluation of metabolic and inflammatory status in patients with CF.